Role of ubiquitin specific proteases in the immune microenvironment of prostate cancer: A new direction - Guo, Jinhui; Zhao, Jie; Sun, Litao; Yang, Chen (Frontiers in Oncology, 2022)
Ubiquitination regulation is involved in multiple processes of tumorigenesis and development, especially in the regulation of the tumor immune microenvironment. Deubiquitinating enzymes (DUBs) can remove ubiquitin chains from substrates, thereby stabilizing target proteins and altering and remodeling biological processes. In tumorigenesis, deubiquitination-altered biological processes are closely related to tumor metabolism, stemness, and the immune microenvironment. Recently, tumor microenvironment (TME) modulation strategies have attracted considerable attention in cancer immunotherapy. Targeting immunosuppressive mechanisms in the TME has revolutionized cancer therapy. Prostate cancer is one of the most common cancers and the second most common cause of cancer-related death in men worldwide. While immune checkpoint inhibition (ICI) has produced meaningful therapeutic effects in many cancer types, clinical trials of anti-CTLA4 or anti-PD1 have not shown a clear advantage in prostate cancer patients. TME affects prostate cancer progression and also enables tumor cell immune evasion by activating the PD-1/PD-L1 axis. Over the past few decades, an increasing number of studies have demonstrated that deubiquitination of the prostate cancer immune microenvironment may modulate the host immune system's immune response to the tumor. As the largest and most diverse group of DUBs, ubiquitin-specific proteases (USPs) play an important role in regulating T cell development and function. According to the current studies, USPs exhibit a high expression signature in prostate cancer and may promote tumorigenesis. The elevated expression of USPs often indicates poor tumor prognosis, suggesting that USPs are expected to develop as the markers of tumor prognosis and even potential drug targets for anti-tumor therapy. In this article, we first summarize recent advances of USPs in prostate cancer. We then focus on the relationship between USPs and immunity. In addition, the resistance mechanisms of USPs to targeted drugs in prostate cancer were clarified. Finally, we reviewed the major achievement of targeting USPs for cancers.